Checkpoint/Restart and Beyond: Resilient High Performance Computing with FPGAs - Schmidt, A G; Bin Huang; Sass, R; French, M (2011 IEEE 19th Annual International Symposium on Field-Programmable Custom Computing Machines, 2011)
As FPGA resources continue to increase, FPGAs present attractive features to the High Performance Computing community. These include the power-efficient computation and application-specific acceleration benefits, as well as tighter integration between compute and I/O resources. This paper considers the ability of an FPGA to address another, increasingly important, feature - resiliency. Specifically, a minimally-invasive monitoring infrastructure operating over a sideband network is presented. This includes a multi-chip protocol, IP cores that implement the protocol, and a tool to instrument existing hardware accelerator FPGA designs. To demonstrate the functionality, the system has been implemented on a cluster of FPGA devices running off-the-shelf MPI and Linux. We demonstrate the ability to do integrated software and hardware accelerator check pointing with restart under a variety of injected faults.